Home blood pressure monitoring and e-Health: investigation of patients' experience with the Hy-Result system. Issue 3 (June 2020) - Postel-Vinay, Nicolas; Steichen, Olivier; Pébelier, Emmanuelle; Persu, Alexandre; Berra, Elena; Bobrie, Guillaume; Savard, Sébastien; Nogueria, José; Azizi, Michel
Abstract : Background: Hy-Result is a validated system designed to help patients complying with the home blood pressure monitoring (HBPM) protocol and understanding their blood pressure (BP) readings. It is available as a standalone web application or within a wireless BP monitor app. Objective: The aim of the study was to explore patients' experience with Hy-Result. Methods: Online survey completed by 512 users of the Hy-Result web application or monitor app, and three focus groups with 24 hypertensive patients who monitor their BP at home and use the Hy-Result web application to record their data. We assessed the experience of patients with the functionalities and medical content of Hy-Result, their feelings and expectations, and the impact of Hy-Result on the physician–patient relationship. Results: (1) Functionalities: Over 90% of survey respondents and all focus group participants found Hy-Result easy to use. The main drawback of the web application is the need to manually enter all BP values at once. (2) Medical content: Hy-Result offers information on arterial hypertension and HBPM that most patients found useful. Users found that Hy-Result triggers appropriate reactions to BP readings, including adequately timed general practitioner visits. (3) Feelings and expectations: Over 90% of survey respondents trust Hy-Result and focus group participants understood that text messages are suggestions, not diagnoses. Hy-Result did not cause anxiety or excessive BP measurements. (4) Physician–patient relationship: Three-quarter of survey respondents agreed that Hy-Result may help when talking with their doctor about their BP values but only one-third of those have shown the report to their physician. For focus group participants, using Hy-Result should ideally be a physician prescription. They were aware that Hy-Result does not replace clinical judgment and that physicians still have a decisive role in BP management. Conclusion: Most of the users described Hy-Result as an easy-to-use and useful tool. Patients are willing to use it on physician request.